Novel naphthenate surfactants based on petroleum acids and nitrogenous bases as corrosion inhibitors for C1018-type mild steel in CO2-saturated brine - Hany M. Abd El-Lateef; V.M. Abbasov; L.I. Aliyeva; Mai M. Khalaf (Egyptian Journal of Petroleum)
The efficiency of two natural naphthenate surfactants (Naphthenic-dimethylamine and Naphthenic-diethylamine complexes), as corrosion inhibitors for mild steel in CO2-saturated 1% NaCl solution, has been determined by linear polarization resistance corrosion rate and potentiodynamic polarization measurements. These compounds inhibit corrosion even at very low concentrations (25 ppm), and Naphthenic-diethylamine complex is the best inhibitor giving maximum inhibition efficiency (99.76) at 100 ppm. Polarization curves indicate that, the two investigated compounds are mixed inhibitors, affecting both cathodic and anodic corrosion currents. Adsorption of naphthenate surfactants on the mild steel surface is in good agreement with the Langmuir adsorption isotherm model, and the calculated Gibbs free energy values confirm the chemical nature of the adsorption. Energy dispersive X-ray fluorescence microscopy (EDRF) and scanning electron microscope (SEM) observations confirmed the existence of such an adsorbed film on the mild steel surface.